The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1128/genomea.01061-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of a Distinct Infectious Bursal Disease Virus

Abstract: Infectious bursal disease virus is a relevant avian pathogen that affects poultry production. Here, we report the full-length coding sequence of the Uruguayan strain dIBDV/UY/2014/2202, isolated from a commercial broiler flock. The strain belongs to the distinct IBDV lineage that is widely distributed in South America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
2
4
0
Order By: Relevance
“…In contrast, there was no significant difference in the VN titer of serum from birds inoculated with F52-70 or 228E against the homologous A1 strain (PBG98/HVR F52-70 ), the A3 strain (PBG98/HVR UK661 ), or the A4 strain (PBG98/HVR M04/09 ), suggesting that these genogroups are antigenically more closely related to genogroup A1 strains, and that vaccines containing the VP2 from genogroup A1 strains may be likely to provide better protection. These data are also consistent with what is observed in the field, where vaccines including the VP2 from genogroup A1 viruses are used to control vv IBDV strains belonging to genogroup A3 (36), and distinct A4 strains in South America (47).…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, there was no significant difference in the VN titer of serum from birds inoculated with F52-70 or 228E against the homologous A1 strain (PBG98/HVR F52-70 ), the A3 strain (PBG98/HVR UK661 ), or the A4 strain (PBG98/HVR M04/09 ), suggesting that these genogroups are antigenically more closely related to genogroup A1 strains, and that vaccines containing the VP2 from genogroup A1 strains may be likely to provide better protection. These data are also consistent with what is observed in the field, where vaccines including the VP2 from genogroup A1 viruses are used to control vv IBDV strains belonging to genogroup A3 (36), and distinct A4 strains in South America (47).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, a mutation at AA position A270E was observed in a vvIBDV isolate with unusual pathogenicity (Hoque et al, 2001) which appeared to influence virulence as observed recently (Lawal et al, 2017). Recent findings in the epidemiology of IBDV revealed the emergence of a distinct strain not known before, designated as distinct IBDV (dIBDV), having unique diagnostic AA sequences 272T, 289P, 290I, and 296F within the VP2 hypervariable region that are conserved and a 234P in the VP1, that is wide spread in South America, Europe and Asia (Hernández et al, 2015;Tomás et al, 2015) and which could not be classified into any of the previously known IBDV strains based on molecular signatures and pathogenicities. For VP1 protein, phylogenetic studies revealed more than one lineage of genome segment B of IBD viruses with high degree of conservation between vvIBDVs and non-vvIBDVs (Hon et al, 2006).…”
Section: Genetic Reassortments In Ibdv Antigenic Drift and Genomic Rna Mutationssupporting
confidence: 53%
“…Interestingly, immunization with one subtypes evokes little or no neutralizing immunity against other subtypes especially when low vaccine doses are being administered . Although vaccination and adequate biosecurity had been the most effective control measures against IBD (Muller et al, 2012;Gelb et al, 2016), the emergence of variant and very virulent IBDV pathotypes in the 1980s (Berg, 2000) and the recent distinct IBDVs (dIBDV) (Tomás et al, 2015;Hernández et al, 2015) threatens the effectiveness of the current available vaccines (Alfonso-Morales et al, 2015). These variant and very-virulent types have been observed to break through maternally derived antibody (MDA) and cause infection in young chickens with mortality up to 60% in pullets and 25% in broilers (van den Berg et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…By analysing the hvVP2 sequences available in the GenBank, we inferred that more than 10% of the IBDV sequences correspond to dIBDVs, suggesting a high frequency of this lineage in the global virus population. Countries such as Argentina, Canada and Uruguay have reported a high prevalence of this lineage circulating in the poultry production, while in countries such as Brazil, Colombia, Hungary, Poland, Puerto Rico, Russia, South Korea and the United States, there are only sporadic reports of dIBDVs (Shcherbakova et al, 1998;Kwon et al, 2000;Ikuta et al, 2001;Jackwood et al, 2001;Smiley & Jackwood, 2001;Domanska et al, 2004;Remorini et al, 2006;Jackwood & Sommer-Wagner, 2007;Ojkic et al, 2007;Hernández et al, 2015;Tomás et al, 2015;Vera et al, 2015). This uneven prevalence among different countries needs to be confirmed by performing more extensive studies with a specific diagnostic method, taking into consideration that dIBDVs can be easily ignored during routine surveillance due to the apparent lack of differential clinical signs (Ikuta et al, 2001;Domanska et al, 2004).…”
Section: Discussionmentioning
confidence: 99%